40 Rubrics & checklists to assess reading and writing - Fiderer, Adele (Scholastic Professional Books, 1999)
"In this sequel to the best-selling book for the primary grades '35 Rubrics and Checklists for Assessing Reading and Writing', Adele Fiderer provides the ready-to-go materials you need to put rubric assessment into practice in grades 3-6. This is the book that will help your students meet the state and national standards in reading and writing."